2023
DOI: 10.1085/jgp.202313375
|View full text |Cite
|
Sign up to set email alerts
|

Epilepsy-associated SCN2A (NaV1.2) variants exhibit diverse and complex functional properties

Abstract: Pathogenic variants in voltage-gated sodium (NaV) channel genes including SCN2A, encoding NaV1.2, are discovered frequently in neurodevelopmental disorders with or without epilepsy. SCN2A is also a high-confidence risk gene for autism spectrum disorder (ASD) and nonsyndromic intellectual disability (ID). Previous work to determine the functional consequences of SCN2A variants yielded a paradigm in which predominantly gain-of-function variants cause neonatal-onset epilepsy, whereas loss-of-function variants are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Moreover, as a result of our cross-channel approach, we were able to apply our calibration beyond SCN1A , which accounts for our benign variant dataset, to an additional 117 variants in SCN2A/3A/8A , which are the causative genes in up to an additional 11% of all genetic epilepsies in large exome studies. 1,2 Given the applicability of some functional insight for a majority of reported individuals with disease-causing SCN2A variants, as well as the rise of automated electrophysiological approaches in the research space, 15-18 we expect that systematic functional evaluations will facilitate diagnosis and expand clinical trial readiness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, as a result of our cross-channel approach, we were able to apply our calibration beyond SCN1A , which accounts for our benign variant dataset, to an additional 117 variants in SCN2A/3A/8A , which are the causative genes in up to an additional 11% of all genetic epilepsies in large exome studies. 1,2 Given the applicability of some functional insight for a majority of reported individuals with disease-causing SCN2A variants, as well as the rise of automated electrophysiological approaches in the research space, 15-18 we expect that systematic functional evaluations will facilitate diagnosis and expand clinical trial readiness.…”
Section: Discussionmentioning
confidence: 99%
“…Voltage clamp experiments are the standard in research for the functional study of voltage-gated ion channel variants, and emerging technologies are rapidly increasing scale and throughput of these assays. 15-18 Rigorously leveraging these data within the ACMG/AMP framework would increase available evidence for variant interpretation. However, reporting of results is sparse and heterogeneous.…”
Section: Introductionmentioning
confidence: 99%
“…These days, risk stratification of ion channelopathies is largely based on changes in the electrophysiological properties of ion channel variants. So far, such risk stratification has been performed not only for a selection of cardiac ion channelopathies, as already outlined in the Introduction section, but also for neuromuscular diseases with Na V 1.4 variants [ 87 ], hearing loss related to KCNQ4 variants [ 88 ], and encephalopathies, including schizophrenia, with CACNA1I variants [ 89 ], and epilepsy with SCN1A [ 90 ], KCNB1 [ 91 ], HCN1 [ 92 ], KCNQ2 [ 93 ], and SCN2A [ 94 ] variants. In the present study, we tested whether risk stratification for sinus bradycardia can be based on AP clamp experiments on transfected cells to compute the charge carried by (mutant) I f during the diastolic depolarization phase of a prerecorded human SAN AP, using this AP as command potential.…”
Section: Discussionmentioning
confidence: 99%
“…It is obvious, then, that Nav1.2 electrophysiologic changes noted in SCN2A mutation-related EE are more complex. Studies have shown that many patients with epilepsy-related SCN2A mutations present with complex GoF or LoF characteristics, and some rare mutations share both characteristics ( 19 , 20 ). Hence, it is difficult to apply a simple scheme with respect to classification.…”
Section: Discussionmentioning
confidence: 99%